Black-Gloss Pottery Found in a Residential Building in Nikonion. Research Seasons 2008-2011 - Głuszek, Inga (Acta Archaeologica Lodziensia, 2021)
The paper concerns the discoveries of tableware made in the black-gloss technique, which were found in a living house uncovered in Nikonion during the excavations in 2008-2011. However, the following paper constitutes a detailed analysis of the discoveries directly related to the usability of the uncovered house. Among the discoveries of black-gloss pottery related to the house’s floor levels the oldest can be dated to the end of the 4th century B.C., most of the discoveries are dated as far as the 3rd century BC. Most of the finds present the products of Attic workshops, but there are three examples of vessels that come from other production centres